Genomic Insights into the Fungal Lignocellulolytic Machinery of Flammulina rossica - Young-Jin Park; Chang-Soo Lee; Won-Sik Kong (Microorganisms, 2019)
Next-generation sequencing (NGS) of the Flammulina rossica (wood-rotting basidiomycete) genome was performed to identify its carbohydrate-active enzymes (CAZymes). De novo genome assembly (31 kmer) revealed a total length of 35,646,506 bp (49.79% GC content). In total, 12,588 gene models of F. rossica were predicted using an ab initio gene prediction tool (AUGUSTUS). Orthologous analysis with other fungal species revealed that 7433 groups contained at least one F. rossica gene. Additionally, 12,033 (95.6%) of 12,588 genes for F. rossica proteins had orthologs among the Dikarya, and F. rossica contained 12 species-specific genes. CAZyme annotation in the F. rossica genome revealed 511 genes predicted to encode CAZymes including 102 auxiliary activities, 236 glycoside hydrolases, 94 glycosyltransferases, 19 polysaccharide lyases, 56 carbohydrate esterases, and 21 carbohydrate binding-modules. Among the 511 genes, several genes were predicted to simultaneously encode two different CAZymes such as glycoside hydrolases (GH) as well as carbohydrate-binding module (CBM). The genome information of F. rossica offers opportunities to understand the wood-degrading machinery of this fungus and will be useful for biotechnological and industrial applications.